NOMENCLATURAL NOTES ON THE SUBFAMILY CYCLOMINAE (COLEOPTERA: CURCULIONIDAE) - Morrone, Juan J. (Acta Entomológica Chilena, 2022)
While working on the cladistic classification of the subfamily Rhytirrhininae, I found that some familygroup ñames (e.g., Aterpinae, Hipporhininae, Somatodinae) were too cióse to it to warrant sepárate subfamily status, so I brought them together under the ñame Somatodinae Schoenherr, 1823 (Morrone & Anderson, 1995; Morrone & Roig-Juñent, 1995). I ignored, however, that Richard Thompson had discovered a complex nomenclatural situation conceming this ñame (Thompson, 1992a), and that the International Commission on Zoological Nomenclature (ICZN, 1994) had suppressed it, placing Somatodinae Lacordaire, 1863 in the Official List of Family-Group Ñames in Zoology. Thus, Somatodinae is not the oldest available ñame for this subfamily and Cyclominae Schoenherr, 1823 (= Hipporhininae Lacordaire, 1863) should be used.